1970
DOI: 10.3329/bjsir.v42i2.472
|View full text |Cite
|
Sign up to set email alerts
|

Study on Energy Input, Output and Energy Use Efficiency of Major Jute Based Cropping Pattern

Abstract: An investigation was undertaken in Jute Research Regional Station, BJRI, Kishoreganj during the period of 2000 -2001 to 2002 -2003 to evaluate the energy input, energy output and output-input ratio of some selected jute based cropping pattern. the result showed that the highest energy input (42,928 MJ ha aman rice-Lentil (2,88,33, ), although the energy output from main product of potato containing cropping pattern was the highest. The energy output from by-product was more compared to main product for all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
3
7
1
Order By: Relevance
“…Regardless of landscape position, the largest contributor to energy consumption in our preliminary study was N fertilizer inputs (data not shown). This agrees with previous reports for other rice cropping systems (Quilty et al, 2014; Khan and Hossain, 2007; Rahman et al, 2015). Mechanization in Bangladesh’s coastal zone is slowly but steadily increasing (Mottaleb et al, 2016), which results in increased fuel use for land preparation.…”
Section: Discussionsupporting
confidence: 93%
“…Regardless of landscape position, the largest contributor to energy consumption in our preliminary study was N fertilizer inputs (data not shown). This agrees with previous reports for other rice cropping systems (Quilty et al, 2014; Khan and Hossain, 2007; Rahman et al, 2015). Mechanization in Bangladesh’s coastal zone is slowly but steadily increasing (Mottaleb et al, 2016), which results in increased fuel use for land preparation.…”
Section: Discussionsupporting
confidence: 93%
“…It can be observed that fertilizer was the main cause of variation of total energy input for the three crops. This is in line with the findings of [1,13]). …”
Section: Fig 2 Energy Input Percentages For (A) Sorghum (B) Wheat (Csupporting
confidence: 82%
“…Total system energy output was estimated using energy equivalents as suggested by many scientists (Khan and Hossain, 2007;Shahin et al, 2008). The energy output was calculated by totalling the energy value of both the main product and by-products.…”
Section: System Energy Outputmentioning
confidence: 99%
“…The degree of soil drying at 22.5 cm was less in 2012-2013 than in 2011-2012. 14.7, 14.7, 15.5, 15.6, 15.8 and 12.5 MJ (adopted from Khan andHossain, 2007 andShahin et al, 2008).…”
Section: Soil Properties Changementioning
confidence: 99%